PENGARUH METODE EJA BERBANTUAN MEDIA FLASH CARD UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN - Suherni, Suherni; Samodra, Touvan Juni; Muskania, Ricka Tesi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the use of the spelling method assisted by flash card media in improving initial reading skills in grade I students of SDN 06 East Mempawah. The main problem in learning to read is the low ability of students to distinguish syllables and recognize letter symbols. This research is a Class Action Research (PTK) which is carried out in two cycles with stages of planning, implementation, observation, and reflection. The data collection technique uses tests. The results of the study showed a significant increase in initial reading ability. In the pre-cycle, the percentage of learning completeness was 24%, increasing to 52% in cycle I, and reaching 96% in cycle II. The average score of students also increased from 71.4 in the first cycle to 85.84 in the second cycle. These results show that the spelling method assisted by flash card media is effective in improving students' initial reading skills.